LEKSIKON BAHASA KEI DALAM LINGKUNGAN KELAUTAN: KAJIAN EKOLINGUISTIK - Renjaan, Meiksyana Raynold (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 21 (2014): September 2014, 2014)
This research describes the lexicon of the Kei language concerning sea environment through the ecolinguistic point of view. The method used in this research is qualitative and supported by quantitative. For the analysis, the ecolinguistic point of view are applied. The test result demonstrated, from a numeric point of view, the oldest groups ages 46 and above had the highest rate 3 (3,3 %) versus the median groups 11 (12,2 %) aged 25- 45, and the drop in the youngest 18 (20 %) aged 15-24). The difference picture had caused by (1) the change of sea ecology, (2) there is continuity less from the old people to young people (3) the dominate of bahasa Indonesia and Melayu Ambon. However, 80 % of Keinese speech community still known and vocalize lexicon orienting in the sea. The maintenance of sea lexicon caused by (1) community source of life, (2) the entity still have in the sea ecology, (3) the intense community interaction with the entity that characterized the sea ecology, and (4) there are local expression that meaning to preserve sea environment. The average understanding rate lexicon is 80% from 72 informan, Therefore, Keinese speech community still known and vocalize lexicon orienting in the sea in daily occasion.
Keywords: ecolinguistic, lexicon, sea ecology, and understanding rate